2008
DOI: 10.14411/eje.2008.042
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of antibacterial response genes from the dung beetle Copris tripartitus (Coleoptera: Scarabaeidae) immunized with Escherichia coli

Abstract: Abstract. Dot blot hybridization of total RNA from normal and bacteria-injected larvae of the dung beetle Copris tripartitus identified 13 cDNA clones that seem to be associated with the immune response. A cDNA encoding a dung beetle homolog of the heat shock protein HSP70 (CTHSP70) was characterized by full-length sequencing and expression pattern analysis. CTHSP70 was upregulated 4 h after bacterial injection, reached maximum level after 8 h, and declined gradually after 16 h. Our data suggest that CTHSP70 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, an alternative mechanism might be antimicrobial properties present on the carapace of the beetle, as found in ants [ 40 ]. Hwang et al [ 41 ] isolated antimicrobial response genes responding to E . coli from the dung beetle Copris triparititus (Coleoptera: Scarabaeidae), indicating natural anti-microbial properties are possessed by at least some dung beetles.…”
Section: Discussionmentioning
confidence: 99%
“…However, an alternative mechanism might be antimicrobial properties present on the carapace of the beetle, as found in ants [ 40 ]. Hwang et al [ 41 ] isolated antimicrobial response genes responding to E . coli from the dung beetle Copris triparititus (Coleoptera: Scarabaeidae), indicating natural anti-microbial properties are possessed by at least some dung beetles.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen individual cDNA transcripts were identified as differentially expressed sequences by the dot blot hybridization [13]. One of the up-regulated genes (hereinafter referred to as Coprisin) is a novel member of a family of antibacterial peptides known as insect defensin-like peptides (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…As an initial screening process, a total of 1862 cDNA clones were randomly selected from a full-length cDNA library, spotted onto Hybond-N membranes (Amersham Biosciences, Uppsala, Sweden) using a 96-well format dot blotter (Bio-RAD) and then hybridized with probes from bacteria-injected larvae as described previously [ 13 ]. Coprisin cDNA clones were identified by a dot blot hybridization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study did not examine specific mechanisms that might underlie this apparent harm to the pathogens, but previous studies suggest some possible directions for future investigation. For dung beetles, it has been suggested that, in addition to the physical damage cause by masticatory and gastrointestinal systems (Miller, Chi‐Rodriguez, & Nichols, ), some insects’ exoskeletons possess antimicrobial properties, perhaps as a means to suppress microbial food competitors also common in faeces (Hwang et al., ). It is also likely that when the dung beetles physically disturbed the manure, the subsequent desiccation of the manure caused a less suitable environment for the pathogen (e.g.…”
Section: Discussionmentioning
confidence: 99%